(untitled) (Orfeu, 2024)
This article reviews the strategies adopted by various authors when applying intertextuality to music. Originating from literary theory, intertextuality examines the crossing of texts and their dialogue. In mu-sic, it addresses the relationships between musical realizations, whether notated or re-corded, complete or in excerpts. The aim of this article is to consolidate and differentiate these approaches. Initially, we present the main intertextual approaches in literature, distinguishing between post-structuralist and structuralist perspectives. Subsequently, we describe and compare their applications in music. Musical intertextuality encompas-ses subareas such as borrowing, influence, and Topic Theory. We also propose the su-barea of pragmatic intertextuality, with both analytical and compositional dimensions. We detail the particularities of these suba-reas and identify characteristics of the poie-tic, esthesic, and immanent processes from the semiotic perspective of Jean-Jacques Nattiez (1990; 2021). We conclude by dis-cussing recent trends in intermediality and adaptation studies. The article dedicates a more extensive section to the transtextuality of Gérard Genette (1997a; 2010), an author still underexplored in music.